Kepemimpinan Pendidikan meliputi Pengertian, Karakteristik, Model, Strategi, serta Keberhasilannya - Alberda Salma Fariha; Imamul Muttaqin (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Educational leadership refers to the capacity of a person to inspire and guide others, whether as individuals or groups, toward achieving common objectives within an educational setting. There are various leadership models, such as transformational, servant, democratic, autocratic, bureaucratic, charismatic, and transactional leadership, each offering different approaches to directing and motivating team members. Effective leadership strategies involve careful strategic planning, transparency, and collaboration, which can enhance a school's competitiveness and improve the quality of education. Successful educational leaders must possess integrity, knowledge, courage, initiative, and serve as role models for their teams. The success of educational leadership is influenced by morality, organizational culture, and rewards, which together create a conducive and productive working environment.